2021
DOI: 10.1073/pnas.2100156118
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic shear dissipation and transmission in lipid bilayers

Abstract: Vital biological processes, such as trafficking, sensing, and motility, are facilitated by cellular lipid membranes, which interact mechanically with surrounding fluids. Such lipid membranes are only a few nanometers thick and composed of a liquid crystalline structure known as the lipid bilayer. Here, we introduce an active, noncontact, two-point microrheology technique combining multiple optical tweezers probes with planar freestanding lipid bilayers accessible on both sides. We use the method to quantify bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 71 publications
5
22
0
Order By: Relevance
“…In contrast, since those in the gel phase behave like a solid, the molecules are not equilibrated and remained on the surface even under the tip interaction, which causes the significantly higher P tip accompanied by an irreversible disruption process. These results are consistent with previous studies that showed viscosity 52 as well as Young's modulus 53 in a gel phase exhibits more than one order of magnitude greater than those in a fluid phase. Note that although SM-AFM is also utilized for evaluating the energy loss during the entire force profile, FM-AFM has the advantage that it can be evaluated at the moment of the hemifusion-and-dissociation processes.…”
Section: Resultssupporting
confidence: 93%
“…In contrast, since those in the gel phase behave like a solid, the molecules are not equilibrated and remained on the surface even under the tip interaction, which causes the significantly higher P tip accompanied by an irreversible disruption process. These results are consistent with previous studies that showed viscosity 52 as well as Young's modulus 53 in a gel phase exhibits more than one order of magnitude greater than those in a fluid phase. Note that although SM-AFM is also utilized for evaluating the energy loss during the entire force profile, FM-AFM has the advantage that it can be evaluated at the moment of the hemifusion-and-dissociation processes.…”
Section: Resultssupporting
confidence: 93%
“…On the other hand, our results will support the quantification of the behavior of inclusions in real set-ups, for instance, in flat anchored or clamped biological or artificial membranes [34][35][36][37][38][39][40]. Particularly, we hope to stimulate by our work quantitative experimental investigations and confirmation of our results.…”
Section: Discussionsupporting
confidence: 72%
“…However, this difference may come from the difficulty of quantifying friction between the bilayer surface and the NPs. 46–48 Considering friction for the case of NPs moving at the bilayer surface, the corrected Stokes–Einstein equation can be expressed as: 46–48 where c ( λ ) is a dimensionless parameter and η m is the membrane viscosity. There are considerable discrepancies between the reported membrane viscosity η m from the motion of particles strongly attached to a lipid bilayer.…”
Section: Resultsmentioning
confidence: 99%
“…However, this difference may come from the difficulty of quantifying friction between the bilayer surface and the NPs. [46][47][48] Considering friction for the case of NPs moving at the bilayer surface, the corrected Stokes-Einstein equation can be expressed as: [46][47][48]…”
Section: Diffusion Of Au Nps At the Bilayer Surface With And Without Bsamentioning
confidence: 99%